Le Code Napoléon : questions sur la genèse d’un mythe - Xavier Martin (Clio@Themis)
A “naive” reading of the Travaux préparatoires to the Napoleon’s Code tends to reveal, on the redactors’s vision of man, an opposite version to the one that some French civil academics still defend. We would be here in the presence of a real myth. When, why and how this myth was born? This article tries to answer, also calling some other people to elucidate the problem.